Early Experience of the First Single-Room Gantry Mounted Active Scanning Proton Therapy System at an Integrated Cancer Center - Forsthoefel, Matthew K.; Ballew, Elizabeth; Unger, Keith R.; Ahn, Peter H.; Rudra, Sonali; Pang, Dalong; Collins, Sean P.; Dritschilo, Anatoly; Harter, William; Paudel, Nitika; Collins, Brian T.; Lischalk, Jonathan W. (Frontiers in Oncology, 2020)
Introduction: Review the early experience with a single-room gantry mounted active scanning proton therapy system. Material and Methods: All patients treated with proton beam radiotherapy (PBT) were enrolled in an institutional review board-approved patient registry. Proton beam radiotherapy was delivered with a 250 MeV gantry mounted synchrocyclotron in a single-room integrated facility within the pre-existing cancer center. Demographic data, cancer diagnoses, treatment technique, and geographic patterns were obtained for all patients. Treatment plans were evaluated for mixed modality therapy. Insurance approval data was collected for all patients treated with PBT. Results: A total of 132 patients were treated with PBT between March 2018 and June 2019. The most common oncologic subsites treated included the central nervous system (22%), gastrointestinal tract (20%), and genitourinary tract (20%). The most common histologies treated included prostate adenocarcinoma (19%), non-small cell lung cancer (10%), primary CNS gliomas (8%), and esophageal cancer (8%). Rationale for PBT treatment included limitation of dose to adjacent critical organs at risk (67%), reirradiation (19%), and patient comorbidities (11%). Patients received at least one x-ray fraction delivered as prescribed (36%) or less commonly due to unplanned machine downtime (34%). Concurrent systemic therapy was administered to 57 patients (43%). Twenty-six patients (20%) were initially denied insurance coverage and required peer-to-peers (65%), written appeals (12%), secondary insurance approval (12%), and comparison x-ray to proton plans (8%) for subsequent approval. Proton beam radiotherapy approval required a median of 17 days from insurance submission. Discussion: Incorporation of PBT into our existing cancer center allowed for multidisciplinary oncologic treatment of a diverse population of patients. Insurance coverage for PBT presents as a significant hurdle and improvements are needed to provide more timely access to necessary oncologic care.